Hungarian Monitoring, 26 June 1990 . [Magyar rádiófigyelő], 1990. június 26 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - USA begins the removal of its chemical weapons from the FRG - Bomb explodes in London Domestic Affairs: - Parliamentary resolution requests exit from the Warsaw Pact - Privatization theories Economy: - Hungarian-Belgian employment cooperation agreement - Agrimpex's wheat transports to the Soviet Union Külpolitika: - Az USA megkezdte a vegyi fegyverek eltávolítását az NSZK-ból - Bomba robbant Londonban Belpolitika: - Az országgyűlés határozatban kéri a kormányt a Varsói Szerződésből való kilépésre - Privatizációs elméletek Gazdaság: - Magyar-belga munkaügyi együttműködési megállapodás - Az Agrimpex búzaszállításai a Szovjetuniónak